THE USE OF AUTONOMOUS WEAPON SYSTEMS IN ARMED CONFLICT : LEGALITY AND CHALLENGES FOR FUTURE WEAPON REGULATION - Andreas Wilia; Diajeng Wulan Christianti (Padjadjaran Journal of International Law, 2019)
AbstractAutonomous Weapon Systems (AWS) has been developed as an alternative weapon system in the battlefield. It has a fundamental difference with other weapons systems which lies in decision making carried out without human intervention. AWS is able to make decisions about life and death and it has been legally, morally and ethically challenged since it has potential to distract moral and ethical on the battlefield. However, as a smart weapon, it gives a significant advantage since it can be deployed in very dangerous areas for the purpose of self-defense in critical situations. This article argues that AWS is still a conventional weapon and cannot be absolutely prohibited even if it is deemed as a vulnerable and destructive weapon which potentially violates international humanitarian law (IHL). AWS is still fully compliant with IHL basic principles for as long as there is a sufficient legal basis that provides the limit and legality of the use of AWS. Accordingly, this article also suggests that the future AWS regulation should be followed by appropriate technical provision on the development, production, ownership, transfer and use in armed conflict.Keywords: Armed Conflict, Autonomous Weapon Systems, International Humanitarian Law, Weapon Regulation AbstrakSistem Senjata Otonom (AWS) telah dikembangkan sebagai sistem senjata alternatif dalam pertempuran dan memiliki perbedaan fundamental dengan sistem senjata lain yaitu, keputusan yang diambil tanpa adanya intervensi manusia. AWS mampu untuk memutuskan hidup dan matinya target kombatan sehingga penggunaannya ditentang baik secara hukum, moral, dan etika karena berpotensi merusak moral dan etika dalam peperangan. Namun demikian, sebagai senjata modern, AWS memberikan keuntungan yang nyata mengingat AWS dapat ditempatkan di daerah yang berbahaya bagi manusia untuk alasan bela diri dalam situasi yang sangat sulit. Penelitian ini menyatakan bahwa AWS tetap merupakan senjata konvensional yang penggunaannya tidak dapat dilarang secara absolut sekalipun berpotensi menjadi senjata penghancur yang dapat melanggar hukum humaniter. AWS mampu untuk mematuhi prinsip-prinsip dasar hukum humaniter sepanjang pengaturan dan pembatasan penggunaannya diatur dalam instrumen hukum humaniter yang memadai yang hingga saat ini belum tersedia. Dengan demikian, penelitian ini menyarankan bahwa aturan AWS masa depan harus juga mencakup aturan-aturan teknis tentang pengembangan, pembuatan, kepemilikan, pengalihan serta penggunaan dari AWS dalam sengketa bersenjata. Kata Kunci: Aturan Senjata, Konflik Bersenjata, Hukum Humaniter Internasional, Sistem Senjata Otonom